USERS OF TOBACCO AND NICOTINE PRODUCTS: KEY BEHAVIORAL TYPES - Taras Gutor; Svitlana Kozii-Bredelieva; Natalia Zaremba; Dmytro Kupyra; Dzvenyslava Moskviak-Lesniak (Acta Medica Leopoliensia)
Aim. Establishing the type of tobacco behavior and the main motives and reasons for smoking among consumers of tobacco products.